Strength of kaolin stabilized with various percentage of lime and 4% silica fume - Mohammad Syafiq, Ideris (2015)
Clay soil as known as soft soil present difficulties to geotechnical engineer due to its complex nature and also contain variable materials. This type of soil can be categorized as problematic soil due to its weak properties. As the preliminary stage, soft clay soil did not meet the requirement for construction purpose. This is because the entire load from the top of the building will be transferred to the underlying soil. As we know the strength of soil is weak, without proper design, modification and earthwork, construction problem such as cracking, settlement of building may be occur and the building may collapse within its design life. It is very risky if the construction is still continuing on this type of soil without any remediation or improvement on the soil itself. Therefore, a proper modification for the soil itself is required to alter the soil become stronger; hence meet the requirement to use in construction industry. There are various methods to improve the soil. This research proposes about soil stabilization method that is soft clay soil Kaolin S300 stabilized with various percentages of lime and 4% silica fume. Percentages of lime used are 3%,5%,7% and 9%. While the percentage of silica fume used is fixed that is 4%. The main objectives in this research is to conduct the improvement of undrained shear strength of soft clay soil mixed with various percentages of lime and 4% silica fume. The improvement will be observed based on different percentage of lime. Other physical and mechanical tests that involves in this study are Atterberg Limit, Falling Head, Standard Compaction, Hydrometer, and Specific Gravity, The properties of soil was compared between the kaolin only and different percentages of lime mixed with 4% silica fume. The main test in this research is unconfined compressive test that is to determine the undrained shear strength. From the study, the optimum amount value of lime is 5%. This is because at 5% lime content, the maximum stress achieve is 29.37 kPa which is optimum compared to others percentage. It is shown that, the strength of soft clay is improved by 14.28%. Based on laboratory test result, it can be concluded that soil stabilization by using lime and silica fume can improved the strength of soft clay. Lastly, after all the tests had been done, correlation equation and cohesion value for each test were list out in graph and tabular form as well